Balancing sustainability and consumer demand: Exploring Gen Z interest in co-designing transformable garments - Zeng, Zhen; Jalil, Marzie Hatef (Edelweiss Applied Science and Technology, 2025)
Transformable Garment Co-Design (TGCD) offers a variety of options and precise targeting, reducing unnecessary purchases and potentially providing a sustainable solution that aligns resource use with consumer demands. Nevertheless, this design strategy remains underutilized in the market and lacks thorough theoretical exploration. This research examines the aesthetic and functional aspects that impact the willingness of Generation Z, the predominant fast-fashion buyers in China, particularly university students, to interact with TGCD. A quantitative method was employed to survey randomly selected university students in Zhejiang Province, China. Data was gathered from 359 respondents through the WeChat social application and the Wenjuanxing questionnaire platform. Hotelling’s t-squared test in SPSS was utilized to evaluate the significance of the proposed factors. The results indicated that aesthetic and functional characteristics and familiarity with TGCD significantly influence Chinese university students’ readiness to adopt this design method. Further analysis revealed that comfort, durability, and types of expertise notably influence this willingness. This study advances sustainable design theory by empirically examining TGCD in China, providing this innovative strategy with an initial framework that can serve as a reference for academia and industry.